2022
DOI: 10.1007/s00068-021-01872-0
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical comparison of acetabular fracture fixation with stand-alone THA or in combination with plating

Abstract: Purpose A common surgical treatment in anterior column acetabular fractures with preexisting osteoarthritis is THA, which is commonly combined with plate osteosynthesis. Implantation of a solitary revision cup cranially fixed to the os ilium is less common. The purpose of this study was to compare the stabilization of anterior column acetabular fractures fixed with a cranial socket revision cup with flange and iliac peg or with a suprapectineal plate osteosynthesis combined with an additional rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…Biomechanical testing was performed on a servohydraulic material test system (Mini Bionix II 858; MTS Systems, Eden Prairie, MN, USA) equipped with a 4 kN load cell (HUPPERT 6, HUPPERT GmbH, Herrenberg, Germany). The setup was adopted from previous biomechanical studies investigating acetabulum fractures [ 19 ] ( Fig 2 ). Each hemi-pelvic was tested and aligned in an inverted upright standing position.…”
Section: Methodsmentioning
confidence: 99%
“…Biomechanical testing was performed on a servohydraulic material test system (Mini Bionix II 858; MTS Systems, Eden Prairie, MN, USA) equipped with a 4 kN load cell (HUPPERT 6, HUPPERT GmbH, Herrenberg, Germany). The setup was adopted from previous biomechanical studies investigating acetabulum fractures [ 19 ] ( Fig 2 ). Each hemi-pelvic was tested and aligned in an inverted upright standing position.…”
Section: Methodsmentioning
confidence: 99%
“…Case 1: A 68-year-old woman presented after a fall following a recent THA performed using a posterior approach. Images showed an isolated fracture of the posterior wall that was classified as a type The Unified Classification System of Periprosthetic Fractures [30]…”
Section: Cup Replacement Without Osteosynthesismentioning
confidence: 99%
“…The concept of the revision cup with flange and pelvic peg involves cranial fixation of the cup into the iliac bone, and containment or press-fit of the cup is not necessary. In a biomechanical study by Wenzl et al, [30] it was shown that the treatment of an anterior column fracture using a cranial socket revision cup with a flange and iliac peg provides the same biomechanical stability as anterior plate osteosynthesis and a revision cup. The advantage of the former surgical method is the single approach and minor surgical trauma.…”
Section: Treatment Strategies For Periprosthetic Acetabular Fracturesmentioning
confidence: 99%
“…Biomechanical testing was run on a material test system (Mini Bionix II 8 Systems, Eden Prairie, MN, USA) equipped with a 4 kN load cell (HUPPERT 6, HU GmbH, Herrenberg, Germany). The setup was implemented from previous stud ure 2) [15]. Each hemi-pelvic specimen was tested in an inverted, upright standi tion, resting on a base plate inclined at 20° to the machine base in the frontal pla the symphyseal medial aspect and the sacroiliac joint were positioned flush with plate in accordance with Morosato et al [16].…”
Section: Biomechanical Testingmentioning
confidence: 99%